Formulations. - Tadros, Tharwat F. (De Gruyter, 2016)
Formulations starts with a general introduction, explaining interaction forces between particles and droplets, self-assembly systems, polymeric surfactants and nanoemulsions. The second part covers the industrial examples ranging from foams, soaps over to hair care, sunscreen and make-up products. Combines information needed by formulation chemists as well as researchers in the cosmetic industry due the increasing number of products.